Between innovation and uncertainty: challenges and perspectives of gamification for medical faculty - Culcay Delgado, Joshua Israel; Soasty Vera, Mildredd Rebeka (Spanish Journal of Medical Education, 2025)
The imperative need for medical educators to acquire skills aligned with the advancement of emerging technologies, generative artificial intelligence, and new teaching organization methods is becoming evident. In this context, playful pedagogical approaches have gained increasing acceptance in the medical field, enabling the consolidation of more structured and automated strategies based on gamification. These strategies foster active student participation, as well as competition, collaboration, and cooperation, considered fundamental pillars of the constructivist and humanist paradigms that currently guide training in medical schools globally. From this perspective, it is necessary to adopt gamification as a disruptive teaching tool within the teaching-learning process in medicine, in order to overcome the dichotomy between the traditional model, centered on the lecturer's oratory and rhetoric, and autonomous learning approaches, in which students can access innovative methodologies supported by gamification.